Lithium secondary battery

By using a lithium nickel-cobalt-manganese-based positive electrode active material and a silicon-based negative electrode active material with a high nickel content in lithium secondary batteries, and using a high concentration of specific lithium salts in a non-aqueous electrolyte solution, the performance deterioration of lithium secondary batteries when combining high nickel and silicon-based materials is solved, and excellent electrochemical characteristics, stability and life characteristics are achieved.

CN119812310APending Publication Date: 2025-04-11LG ENERGY SOLUTION LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202510232885.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2018-05-11
Filing Date
2019-05-10
Publication Date
2025-04-11

AI Technical Summary

Technical Problem

When the existing lithium secondary batteries combine the positive electrode active material with a high nickel content and the silicon-based negative electrode active material, there are problems such as sharp deterioration of battery performance, structural instability and negative electrode deterioration.

Method used

A high nickel content of lithium nickel cobalt manganese-based positive electrode active material and silicon-based negative electrode active material were used, and a high concentration of LiPF6 and bis(fluorosulfonyl)imide lithium were used in the non-aqueous electrolyte solution to form a stable SEI film to inhibit the dissolution of metal ions and the expansion of the negative electrode.

Benefits of technology

The excellent electrochemical characteristics, stability and life characteristics of lithium secondary batteries are achieved, while the capacity characteristics and thermal stability are improved, and the structural instability of high-nickel electrodes is reduced.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119812310A_ABST
    Figure CN119812310A_ABST
Patent Text Reader

Abstract

The present invention relates to a lithium secondary battery comprising: a positive electrode containing a lithium nickel cobalt manganese-based positive electrode active material in which the nickel content is at least 80 mol% with respect to the total amount of transition metals; a negative electrode containing a silicon-based negative electrode active material and a carbon-based negative electrode active material in a weight ratio of 1: 99 to 50: 50; a diaphragm; and a non-aqueous electrolyte solution containing a non-aqueous organic solvent and a lithium salt, in which the concentration of the lithium salt is 1.8 M to 5 M, and the lithium salt contains LiPF6 and lithium bis (fluorosulfonyl) imide.
Need to check novelty before this filing date? Find Prior Art

Description

[0001] This application is a divisional application of PCT international application PCT / KR2019 / 005632 with an application date of May 10, 2019. The original application is a patent application for an invention, and the application number for entering the Chinese national phase is 201980006703.6, with the title "Lithium secondary battery". Technical Field

[0002] The present invention relates to a lithium secondary battery, and more particularly, to a lithium secondary battery having high capacity characteristics, excellent life characteristics, electrochemical characteristics, and stability. Background Art

[0003] With the growing interest in new renewable energy that can replace nuclear energy and fossil fuels due to recent environmental problems, the demand for secondary batteries in new renewable energy has increased sharply, and they have a semi-permanent life characteristic that can be charged and discharged for repeated use.

[0004] Among them, lithium secondary batteries have become the most concerned secondary batteries due to their excellent life characteristics and high energy density. As cathode active materials, various lithium transition metal oxides have been developed, such as LiCoO2, LiNiO2, LiMnO2, LiMn2O4, LiFePO4, Li(Ni a Co b Mn c )O2 (where a, b, and c are the atomic fractions of the respective independent oxide constituent elements, 0 < a < 1, 0 < b < 1, 0 < c < 1, and a + b + c = 1, hereinafter referred to as NCM-based lithium oxides). Among these metal oxides, high-Ni NCM-based lithium oxides with an increasing nickel content are currently being actively developed to meet high capacity characteristics. As the nickel content of the NCM-based lithium oxides increases, there are advantages in terms of achieving capacity, but due to poor structural stability and the dissolution of transition metal components due to reaction with the electrolyte, there is a problem of a sharp deterioration in battery performance. In particular, when the nickel content in the cathode active material is 80 mol% or more among all transition metals, this problem is very obvious.

[0005] Meanwhile, carbonaceous materials such as graphite have been mainly used as anode active materials for lithium secondary batteries, but recently, technologies including silicon-based materials as anode active materials are being developed. Since silicon-based materials have a higher theoretical capacity than carbon-based materials, they have the advantage of being able to achieve high capacity characteristics. However, due to a high irreversible capacity, silicon-based materials have problems of low initial capacity and high initial resistance. In addition, due to volume expansion during charge and discharge, there is a problem of reduced battery life.

[0006] In addition, when a silicon-based negative electrode active material is used together with a positive electrode active material having a high nickel content, since metal ions eluted from the positive electrode active material hinder the formation of SEI (solid electrolyte interphase) on the surface of the negative electrode, there is a problem that it is difficult to form a stable film, thereby accelerating the deterioration of the negative electrode performance.

[0007] Therefore, there is a need to develop a lithium secondary battery having excellent electrochemical characteristics, stability, and life characteristics while achieving high-capacity characteristics. SUMMARY OF THE INVENTION

[0008] Technical issues

[0009] To solve the above problems, the present invention provides a lithium secondary battery having excellent electrochemical characteristics, stability, and life characteristics, and using active materials having high-capacity characteristics for both the positive electrode and the negative electrode.

[0010] Technical Solution

[0011] In one aspect of the present invention, there is provided a lithium secondary battery, the lithium secondary battery comprising: a positive electrode comprising a lithium nickel cobalt manganese-based positive electrode active material, wherein, among all transition metals, the content of nickel is 80 mol% or more; a negative electrode comprising a silicon-based negative electrode active material; a separator; and a non-aqueous electrolyte solution, wherein the non-aqueous electrolyte solution comprises a non-aqueous organic solvent and a lithium salt, the concentration of the lithium salt is 1.8 M to 5 M, and the lithium salt comprises LiPF6 and lithium bis(fluorosulfonyl)imide. Here, the weight ratio of LiPF6 and lithium bis(fluorosulfonyl)imide comprised is preferably 1:9 to 5:5.

[0012] The positive electrode active material can be represented by the following Formula 1.

[0013] [Formula 1]

[0014] Li 1+x [Ni a Co b Mn c M d O2

[0015] In Formula 1 above, 0 ≤ x < 1, 0.8 ≤ a < 1, 0 < b < 0.2, 0 < c < 0.2, 0 ≤ d < 0.2, and M is at least one element selected from the group consisting of W, Cu, Fe, V, Cr, Ti, Zr, Zn, Al, Ta, Y, In, La, Sr, Ga, Sc, Gd, Sm, Ca, Ce, Nb, Mg, B, and Mo.

[0016] The silicon-based negative electrode active material may include at least one selected from the group consisting of metal silicon (Si), silicon oxide (SiO y ), silicon carbide (SiC) and silicon alloys (Si alloys).

[0017] Meanwhile, the negative electrode may further include a carbon-based negative electrode active material, and in this case, the weight ratio of the silicon-based negative electrode active material and the carbon-based negative electrode active material included is 1:99 to 50:50.

[0018] Meanwhile, the nonaqueous organic solvent may include at least one selected from the group consisting of cyclic carbonate solvents, linear carbonate solvents, ester solvents and ether solvents, and preferably, the nonaqueous organic solvent contains 20 volume % or less of the cyclic carbonate solvent.

[0019] Beneficial Effects

[0020] The lithium secondary battery of the present invention comprises a lithium nickel cobalt manganese-based positive electrode active material (in which the content of nickel among all transition metals is 80 mol % or more) and a silicon-based negative electrode active material, and thus has excellent characteristics.

[0021] In addition, the lithium secondary battery of the present invention contains a high concentration of lithium salt of 1.8M to 5M in the non-aqueous electrolyte, thereby improving the oxidation stability and heat generation characteristics of the lithium nickel cobalt manganese-based positive electrode active material (wherein the nickel content is 80 mol% or more among all transition metals), and minimizing the occurrence of negative electrode degradation when the positive electrode active material with a high nickel content and the silicon-based negative electrode active material are used together, thereby achieving excellent life characteristics and thermal stability.

[0022] Furthermore, the lithium secondary battery of the present invention uses two specific lithium salts, thereby minimizing the initial capacity reduction and initial resistance characteristics of the silicon-based negative electrode active material. BRIEF DESCRIPTION OF THE DRAWINGS

[0023] Figure 1 It is a graph showing the change of temperature and voltage over time when the HOT box test is performed on the lithium secondary battery manufactured in Example 1 of the present invention.

[0024] Figure 2 It is a graph showing the changes in temperature and voltage over time when the HOT box test is performed on the lithium secondary battery manufactured in Comparative Example 3 of the present invention. DETAILED DESCRIPTION

[0025] Hereinafter, the present invention will be described in more detail.

[0026] It will be understood that the words or terms used in the specification and claims should not be interpreted as limited to the general or dictionary meanings, but should be interpreted as meanings and concepts consistent with the technical spirit of the present invention based on the concepts that the inventor can appropriately define the terms to best explain the principles of the present invention.

[0027] The terms used herein are for the purpose of describing exemplary embodiments only and are not intended to limit the present invention. Unless the context clearly indicates otherwise, a singular expression includes a plural expression.

[0028] It will be understood that when the terms "comprises (comprising)", "provided (set) with" or "having" are used in the specification, it is intended to specify the presence of the stated features, values, steps, elements or a combination thereof, but does not exclude the presence or addition of one or more other features, values, steps, elements or a combination thereof.

[0029] Unless otherwise specified, "%" used in the specification means weight %.

[0030] Specifically, one aspect of the present invention provides a lithium secondary battery, which includes: a positive electrode, which contains a lithium nickel cobalt manganese-based positive electrode active material, wherein the content of nickel in all transition metals is 80 mol% or more; a negative electrode, which contains a silicon-based negative electrode active material; a separator; and a non-aqueous electrolyte solution, wherein the non-aqueous electrolyte solution contains a non-aqueous organic solvent and a lithium salt, the concentration of the lithium salt is 1.8M to 5M, and the lithium salt includes LiPF6 and lithium bis(fluorosulfonyl)imide.

[0031] The positive electrode, negative electrode and separator constituting the lithium secondary battery of the present invention can be manufactured and used in a conventional manner.

[0032] The positive electrode can be manufactured by forming a positive electrode mixture layer on a positive electrode current collector. The positive electrode mixture layer can be manufactured by coating the positive electrode current collector with a positive electrode slurry containing a positive electrode active material, a binder, a conductive material, and a solvent, and then drying and rolling the coated positive electrode current collector.

[0033] The positive electrode collector is not particularly limited as long as it has conductivity and does not cause chemical changes in the battery. For example, stainless steel, aluminum, nickel, titanium, fired carbon, or aluminum or stainless steel surface-treated with carbon, nickel, titanium or silver can be used.

[0034] Here, the positive electrode active material includes:

[0035] A lithium nickel cobalt manganese-based positive electrode active material, wherein the content of nickel in all transition metals is 80 mol % or more. Specifically, the positive electrode active material can be represented by the following formula 1.

[0036] [Formula 1]

[0037] Li 1+x [Ni a Co b Mn c M d O2

[0038] In the above formula (1), 0 ≤ x < 1, 0.8 ≤ a < 1, 0 < b < 0.2, 0 < c < 0.2, 0 ≤ d < 0.2, and M is at least one element selected from the group consisting of W, Cu, Fe, V, Cr, Ti, Zr, Zn, Al, Ta, Y, In, La, Sr, Ga, Sc, Gd, Sm, Ca, Ce, Nb, Mg, B, and Mo.

[0039] As described above, since the lithium nickel cobalt manganese-based positive electrode active material having a high nickel content has a high energy density, high capacity and high output characteristics can be achieved when it is used. However, in the case of the compound represented by the above formula (1) (which is a high-content nickel (Hi-Ni) oxide having a molar ratio of Ni of 80 mol% or more), during the charge and discharge process, a cation mixing phenomenon occurs, in which Li +1 ions and Ni +2 ions change positions in the layered structure of the positive electrode active material. This phenomenon occurs because Li +1 ions are similar in size to Ni +2 ions. When nickel atoms and transition metal atoms having d-orbitals are coordinated and bonded in a high-temperature environment, as the oxidation value of Ni contained in the positive electrode active material changes, the positive electrode active material should have an octahedral structure. However, due to a heterogeneous reaction in which the energy level order is reversed due to external energy supply or oxidation value change, a distorted octahedron is formed, resulting in distortion and collapse of the crystal structure of the positive electrode active material. In addition, another side reaction will occur during high-temperature storage, in which transition metals (especially nickel metal) dissolve out from the positive electrode active material due to the side reaction between the positive electrode active material and the electrolyte. When such a side reaction occurs, the performance of the entire secondary battery is likely to deteriorate due to the structural collapse of the positive electrode active material and the consumption of the electrolyte in the secondary battery. In addition, there is the following problem, in which the dissolved nickel metal will inhibit the formation of the SEI film on the negative electrode surface, thereby accelerating the deterioration of the negative electrode.

[0040] Therefore, the lithium secondary battery of the present invention uses a non-aqueous electrolyte solution containing two specific lithium salts at a high concentration as described above and a positive electrode active material having a high nickel content. Therefore, the side reaction between the positive electrode and the electrolyte solution is effectively suppressed, and the metal dissolution phenomenon is effectively suppressed, thereby reducing the structural instability of the high-capacity electrode.

[0041] With particular reference to this, as described in the present invention, when a lithium salt is contained in a non-aqueous electrolyte solution at a high concentration, the decomposition reaction of the electrolyte solution is reduced due to the decrease in the amount of free solvent (non-solvated solvent) that does not participate in the dissociation of positive ions and negative ions in the electrolyte solution, and the solubility of metal ions is reduced due to the increase in the amount of solvent combined with lithium ions, thereby suppressing the additional dissolution phenomenon of metal ions.

[0042] Therefore, since sufficient amounts of nickel and transition metals for ensuring the capacity of the lithium secondary battery are secured, the energy density is increased, and degradation of the output characteristics can be prevented, and degradation of the negative electrode due to metal elution can also be prevented.

[0043] The content of the positive electrode active material may be 80 wt % to 99.5 wt %, particularly 85 wt % to 95 wt %, based on the total weight of the solids in the positive electrode slurry. If the content of the positive electrode active material is less than 80 wt %, the energy density may be reduced, and thus the capacity may be reduced.

[0044] In addition, as one of the positive electrode slurry components, the binder is a component that helps the bonding between the active material and the conductive material and the bonding with the collector, and the content of the binder is generally 1 wt % to 30 wt % based on the total weight of the solids in the positive electrode slurry. Examples of the binder may be polyvinylidene fluoride, polyvinyl alcohol, carboxymethyl cellulose (CMC), starch, hydroxypropyl cellulose, regenerated cellulose, polyvinyl pyrrolidone, tetrafluoroethylene, polyethylene (PE), polypropylene, ethylene-propylene-diene terpolymer (EPDM), sulfonated EPDM, styrene-butadiene rubber, fluororubber, and various copolymers.

[0045] In addition, the conductive material as one of the components of the positive electrode slurry is not particularly limited as long as it has conductivity without causing chemical changes in the battery. Examples of conductive materials include the following conductive materials: carbon powder, such as carbon black, acetylene black, ketjen black, channel black, furnace black, lamp black or thermal black; graphite powder, such as natural graphite, artificial graphite or graphite with a fully developed crystal structure; conductive fibers, such as carbon fibers or metal fibers; metal powders, such as carbon fluoride powders, aluminum powders and nickel powders; conductive whiskers, such as zinc oxide or potassium titanate; conductive metal oxides, such as titanium oxide; or polyphenylene derivatives. Typically, the content of the conductive material is 1% to 30% by weight based on the total weight of the solids of the positive electrode slurry.

[0046] The average particle size of the conductive material (D 50) may be 10 μm or less, particularly 0.01 μm to 10 μm, and more particularly 0.01 μm to 1 μm. Here, when the average particle size of the conductive material exceeds 10 μm, the dispersibility is poor, resulting in an insignificant conductivity improvement effect due to the addition of graphite powder. Therefore, a conductive material having an average particle size exceeding 10 μm is undesirable.

[0047] As the conductive material, commercially available products may be used, such as products under the name of Chevron Chemical Company or Denka black (Denka Singapore Private Limited), Gulf Oil Company products, Ketjen black, EC-type (Armak Company products), Vulcan XC-72 (Cabot Company products), and Super P (Timcal Co. products) which are acetylene black-type products.

[0048] In addition, the solvent may include an organic solvent such as N-methyl-2-pyrrolidone (NMP), and may be used in an amount that satisfies the desired viscosity when the positive electrode active material is included and optionally includes a binder and a conductive agent. For example, the solvent included may be such that the concentration of the solids in the slurry containing the positive electrode active material and optionally including a binder and a conductive agent is 10 wt % to 60 wt %, and preferably 20 wt % to 50 wt %.

[0049] In addition, the negative electrode can be manufactured by forming a negative electrode mixture layer on a negative electrode collector. The negative electrode mixture layer can be manufactured by coating the negative electrode collector with a negative electrode slurry containing a negative electrode active material, a binder, a conductive material and a solvent, and then drying and rolling the coated negative electrode collector.

[0050] The thickness of the negative electrode collector is generally 3 μm to 500 μm. The negative electrode collector is not particularly limited as long as it has high conductivity without causing chemical changes in the battery. Examples of conductive materials include copper, stainless steel, aluminum, nickel, titanium, fired carbon, copper or stainless steel surface-treated with carbon, nickel, titanium, silver, etc., or aluminum-cadmium alloys, etc. In addition, similar to the positive electrode collector, the negative electrode collector may have fine concave-convex objects on its surface to improve the bonding strength with the negative electrode active material, and the negative electrode collector may be used in various shapes, such as films, sheets, foils, nets, porous bodies, foams, and non-woven fabrics, etc.

[0051] Meanwhile, the negative electrode active material may include a silicon-based negative electrode active material. Specifically, the silicon-based negative electrode active material may include: metal silicon (Si), silicon oxide (SiO y, wherein, 0 < y < 2), silicon carbide (SiC), and Si-Y alloy (where Y is an element selected from the group consisting of alkali metals, alkaline earth metals, group 13 elements, group 14 elements, transition metals, rare earth elements, and combinations thereof, and does not include Si). The element Y can be selected, for example, from the group consisting of the following elements: Mg, Ca, Sr, Ba, Ra, Sc, Y, Ti, Zr, Hf, Rf, V, Nb, Ta, Db, Cr, Mo, W, Sg, Tc, Re, Bh, Fe, Pb, Ru, Os, Hs, Rh, Ir, Pd, Pt, Cu, Ag, Au, Zn, Cd, B, Al, Ga, Sn, In, Ti, Ge, P, As, Sb, Bi, S, Se, Te, Po, and combinations thereof.

[0052] In addition to the silicon-based anode active material, the anode active material may further include a carbon-based anode active material. As the carbon-based anode active material, various carbon-based anode active materials available in the art can be used, such as artificial graphite, natural graphite, graphitized carbon fiber, and amorphous carbon. At the same time, low-crystalline carbon and high-crystalline carbon can be used as the carbon-based anode active material. Representative examples of low-crystalline carbon may include soft carbon and hard carbon, while representative examples of high-crystalline carbon may include irregular, planar, flaky, spherical, or fibrous natural graphite or artificial graphite, Kish graphite, pyrolytic carbon, mesophase pitch-based carbon fiber, mesophase carbon microbeads, mesophase pitch, and high-temperature sintered carbon, such as petroleum or coal tar pitch-derived coke.

[0053] Preferably, the anode active material may be a mixture of a silicon-based anode active material and a carbon-based anode active material, and herein, the mixing ratio (by weight) of the silicon-based anode active material and the carbon-based anode active material may be from 1:99 to 50:50, preferably from 5:95 to 30:70. When the mixing ratio of the silicon-based anode active material and the carbon-based anode active material satisfies the above range, excellent cycle performance can be ensured while improving the capacity characteristics due to the suppression of the volume expansion of the silicon-based anode active material.

[0054] Based on the total solids in the anode slurry, the content of the anode active material may be 80% to 99% by weight.

[0055] In addition, as one of the negative electrode slurry components, the binder is a component that helps the bonding between the active material and the conductive material and the bonding with the collector, and the content of the binder is generally 1 wt % to 30 wt % based on the total weight of the solids in the negative electrode slurry. Examples of the binder may be polyvinylidene fluoride, polyvinyl alcohol, carboxymethyl cellulose (CMC), starch, hydroxypropyl cellulose, regenerated cellulose, polyvinyl pyrrolidone, tetrafluoroethylene, polyethylene (PE), polypropylene, ethylene-propylene-diene terpolymer (EPDM), sulfonated EPDM, styrene-butadiene rubber, fluororubber, and various copolymers.

[0056] The conductive material is a component used to further improve the conductivity of the negative electrode active material. The conductive material is not particularly limited as long as it has conductivity without causing chemical changes in the battery. Examples of conductive materials include the following conductive materials: carbon powder, such as carbon black, acetylene black, ketjen black, channel black, furnace black, lamp black or thermal black; graphite powder, such as natural graphite, artificial graphite or graphite with a fully developed crystal structure; conductive fibers, such as carbon fibers or metal fibers; metal powders, such as carbon fluoride powders, aluminum powders and nickel powders; conductive whiskers, such as zinc oxide or potassium titanate; conductive metal oxides, such as titanium oxide; or polyphenylene derivatives.

[0057] The solvent may include water or an organic solvent such as NMP or alcohol, and may be used in an amount that satisfies a desired viscosity when containing a negative electrode active material and optionally containing a binder and a conductive agent, etc. For example, the solvent may be included so that the concentration of the solid content in the slurry containing the negative electrode active material and optionally containing a binder and a conductive agent is 50 wt % to 75 wt %, and preferably 50 wt % to 65 wt %.

[0058] In addition, in the lithium secondary battery of one embodiment of the present invention, the separator plays a role of preventing an internal short circuit between two electrodes and impregnating an electrolyte, and may be a porous separator conventionally used in the technical field of secondary batteries.

[0059] As the separator, for example, a porous polymer film formed of a polyolefin polymer (e.g., ethylene homopolymer, propylene homopolymer, ethylene / butene copolymer, ethylene / hexene copolymer, and ethylene / methacrylate copolymer) may be used alone or in a laminated form, or a typical porous nonwoven fabric may be used, for example, a nonwoven fabric formed of high melting point glass fiber or polyethylene terephthalate fiber, etc. However, the separator is not limited thereto.

[0060] Alternatively, as the separator, a separator formed by mixing a polymer resin, a filler and a solvent to prepare a separator composition, then directly coating the top of the electrode with the separator composition, and drying the separator composition to form a separator can be used, or another separator formed by casting the separator composition on a support and drying it, and then laminating the separator peeled off from the support on the electrode can be used.

[0061] Here, the porous membrane may generally have a pore size of 0.01 μm to 50 μm and a porosity of 5% to 95%. Also, the porous membrane may generally have a thickness of 5 μm to 300 μm.

[0062] Furthermore, a lithium secondary battery according to one embodiment of the present invention includes a non-aqueous electrolyte solution containing a non-aqueous organic solvent and a lithium salt.

[0063] In the present invention, the lithium salt includes LiPF6 and lithium bis(fluorosulfonyl)imide.

[0064] LiPF6 has excellent electrochemical stability and high ionic conductivity.

[0065] Lithium bis(fluorosulfonyl)imide can form a stable SEI film on the surface of the silicon-based negative electrode active material, thereby inhibiting the reduction reaction of silicon with the electrolyte solution and inhibiting the expansion of the negative electrode. In addition, the SEI film formed by lithium bis(fluorosulfonyl)imide has high stability at high temperatures, thereby achieving the effect of improving the thermal stability of the battery.

[0066] Therefore, when LiPF6 and lithium bis(fluorosulfonyl)imide are used together as in the present invention, a secondary battery having excellent lithium ion conductivity, excellent electrode stability, and excellent thermal stability can be obtained.

[0067] At the same time, the weight ratio of the contained LiPF6 and lithium bis(fluorosulfonyl)imide can be 1:9 to 5:5, preferably 2:8 to 5:5. When the mixing ratio of LiPF6 and lithium bis(fluorosulfonyl)imide satisfies the above range, a SEI film can be stably formed on the surface of the negative electrode containing the silicon-based negative electrode active material, thereby manufacturing a secondary battery with excellent stability.

[0068] Meanwhile, the non-aqueous electrolyte solution of the present invention contains a lithium salt at a concentration of 1.8 M to 5 M, preferably 2 M to 5 M, and more preferably 2 M to 4 M. The research of the present inventors shows the following effects: As mentioned above, when the lithium salt is present at a high concentration in the non-aqueous electrolyte solution in a lithium secondary battery using a positive electrode active material with a high nickel content and a silicon-based negative electrode active material, its lithium ion mobility, oxidation stability and heat generation characteristics are improved.

[0069] Specifically, when the lithium salt concentration in the non-aqueous electrolyte solution is above 1.8M, the hopping phenomenon of lithium ions occurs, so the mobility of lithium ions is improved, and the free solvent is reduced, thereby inhibiting the dissolution of metal ions. In addition, the film formed by the high concentration of lithium salt prevents the silicon volume expansion generated during the charge / discharge process of the lithium secondary battery, thereby inhibiting performance degradation, and the thermal stability of the lithium secondary battery is improved due to the stable existence of the film at high temperature. On the other hand, when the lithium salt concentration in the non-aqueous electrolyte solution exceeds 5M, there is a problem that the lithium salt does not dissociate and it is difficult to drive the battery.

[0070] Meanwhile, it is preferred to use at least one solvent selected from the group consisting of cyclic carbonate-based solvents, linear carbonate-based solvents, ester-based solvents, and ether-based solvents as the non-aqueous organic solvent.

[0071] Here, the non-aqueous organic solvent may include 20% by volume or less, preferably 1% by volume to 20% by volume, more preferably 5% by volume to 15% by volume of a cyclic carbonate solvent. When the content of the cyclic carbonate solvent exceeds 20% by volume, there is a problem that the surface tension and viscosity of the non-aqueous electrolyte solution increase so that the wetting characteristics deteriorate. Moreover, since the cyclic carbonate has high metal ion solubility and high reduction decomposition potential, when the non-aqueous organic solvent contains an excessive amount of cyclic carbonate, it is possible to promote the metal ion dissolution of the positive active material with a high nickel content, and when the cyclic carbonate is used together with a high concentration of salt, due to the formation of an overly thick SEI film on the surface, the performance of the battery may deteriorate.

[0072] Specific examples of the cyclic carbonate solvent are at least one selected from the group consisting of ethylene carbonate (EC), propylene carbonate (PC), 1,2-butylene carbonate, 2,3-butylene carbonate, 1,2-pentanediol carbonate, 2,3-pentanediol carbonate, vinylene carbonate and fluoroethylene carbonate (FEC), but are not limited thereto.

[0073] In addition, specific examples of the linear carbonate solvent are at least one selected from the group consisting of the following substances or a mixture of at least two thereof: selected from dimethyl carbonate (DMC), diethyl carbonate (DEC), dipropyl carbonate, ethyl methyl carbonate (EMC), methylpropyl carbonate and ethylpropyl carbonate, but are not limited thereto.

[0074] As the ester solvent, a linear ester solvent, a cyclic ester solvent or a combination thereof may be used.

[0075] Specific examples of the linear ester solvent are at least one selected from the group consisting of methyl acetate, ethyl acetate, propyl acetate, methyl propionate, ethyl propionate, propyl propionate and butyl propionate, but are not limited thereto.

[0076] In addition, specific examples of the cyclic ester solvent are at least one selected from the group consisting of γ-butyrolactone, γ-valerolactone, γ-caprolactone, α-valerolactone and ε-caprolactone or a mixture containing at least two thereof, but are not limited thereto.

[0077] Meanwhile, specific examples of the ether solvent are at least one selected from the group consisting of dimethyl ether, diethyl ether, dipropyl ether, methyl ethyl ether, methyl propyl ether and ethyl propyl ether, but are not limited thereto.

[0078] Preferably, the non-aqueous electrolyte solution of the present invention may be a mixed solvent comprising a cyclic carbonate solvent and a linear carbonate solvent, and here, the mixing ratio (volume ratio) of the cyclic carbonate solvent and the linear carbonate solvent may be 1:99 to 20:80, preferably 5:95 to 20:80.

[0079] Meanwhile, the nonaqueous electrolyte solution of the present invention may further include additives in addition to the lithium salt and the organic solvent, as required.

[0080] The additive includes vinylene carbonate (VC), oxalyl difluoroborate (ODFB), vinyl ethylene carbonate (VEC), succinic anhydride (SA), succinonitrile (SN), 1,3-propane sultone (PS) or a combination thereof. Preferably, the additive includes vinylene carbonate (VC), most preferably vinylene carbonate (VC) and propane sultone (PS). When the non-aqueous electrolyte solution is added with an additive to manufacture a secondary battery, the additive can form a stable SEI film on the negative electrode together with the lithium salt, thereby improving the output characteristics and preventing the oxidation reaction of the electrolyte solution by suppressing the decomposition of the positive electrode surface. Therefore, the output characteristics of the secondary battery can be effectively improved.

[0081] Relative to the total weight of the non-aqueous electrolyte solution, the content of the additive may be 0.1 wt % to 10 wt %, and preferably 0.5 wt % to 3 wt %. When the content of the additive is less than 0.1 wt %, the effect of improving the low temperature output and high temperature stability of the secondary battery may not be obvious, and when the content of the additive exceeds 10 wt %, the side reaction in the electrolyte solution may occur excessively. In particular, when the additive is excessively added to the non-aqueous electrolyte solution, the additive may not be fully decomposed at high temperature and exists as an unreacted material at room temperature, thereby deteriorating the life or resistance characteristics of the secondary battery.

[0082] The shape of the lithium secondary battery of the present invention is not particularly limited, but a cylindrical type, a prismatic type, a pouch type, or a coin type may be variously applied according to the purpose to be performed. The lithium secondary battery of the embodiment of the present invention may be a pouch type secondary battery.

[0083] Best Mode for Carrying Out the Invention

[0084] Example 1

[0085] (Preparation of non-aqueous electrolyte solution)

[0086] A non-aqueous electrolyte solution was prepared by adding 2 g of vinylene carbonate (VC) and 1 g of propane sultone (PS) to 97 g of a non-aqueous organic solvent (a solvent mixture of ethylene carbonate and dimethyl carbonate in a volume ratio of 1:9) in which 1.0 M LiPF6 and 1.0 M lithium bis(fluorosulfonyl)imide were dissolved.

[0087] (Manufacturing of Secondary Batteries)

[0088] LiNi as the positive electrode active material 0.8 Co 0.1 Mn 0.1 O2 (NCM811), Super-P as a conductive material, and polyvinylidene fluoride (PVdF) as a binder were added to N-methyl-2-pyrrolidone (NMP) at a weight ratio of 95:2:3 to prepare a positive electrode slurry (solid content: 17 wt%). A 20 μm thick positive electrode collector (Al film) was coated with the positive electrode slurry, dried, and rolled to produce a positive electrode.

[0089] Next, a mixture in which graphite and SiO2 were mixed at a weight ratio of 95:5 (graphite:SiO2) as a negative active electrode, Super-P as a conductive material, and a mixture in which styrene-butadiene rubber (SBR) and carboxymethyl cellulose (CMC) were mixed at a weight ratio of 7:3 (SBR:CMC) as a binder were added to N-methyl-2-pyrrolidone (NMP) at a weight ratio of 97:1:2 to prepare a negative electrode slurry (solid content: 25 wt%). A 20 μm thick negative electrode collector (Cu film) was coated with the negative electrode slurry, dried, and rolled to manufacture a negative electrode.

[0090] Next, a pouch type battery (2 Ah) was manufactured by a conventional method in which the manufactured positive electrode and negative electrode were sequentially laminated with a polyethylene porous film and then the non-aqueous electrolyte solution prepared above was injected, thereby manufacturing a lithium secondary battery.

[0091] Example 2

[0092] A lithium secondary battery was manufactured in the same manner as in Example 1, except that a non-aqueous electrolyte solution was prepared by adding 2 g of vinylene carbonate (VC) and 1 g of propane sultone (PS) to 97 g of a non-aqueous organic solvent (a solvent mixture of ethylene carbonate and dimethyl carbonate in a volume ratio of 1:9) in which 0.6 M LiPF6 and 1.4 M lithium bis(fluorosulfonyl)imide were dissolved.

[0093] Example 3

[0094] A lithium secondary battery was manufactured in the same manner as in Example 1, except that a non-aqueous electrolyte solution was prepared by adding 2 g of vinylene carbonate (VC) and 1 g of propane sultone (PS) to 97 g of a non-aqueous organic solvent (a solvent mixture of ethylene carbonate and dimethyl carbonate in a volume ratio of 1:9) in which 0.5 M LiPF6 and 1.5 M lithium bis(fluorosulfonyl)imide were dissolved.

[0095] Example 4

[0096] A lithium secondary battery was manufactured in the same manner as in Example 1, except that a non-aqueous electrolyte solution was prepared by adding 2 g of vinylene carbonate (VC) and 1 g of propane sultone (PS) to 97 g of a non-aqueous organic solvent (a solvent mixture of ethylene carbonate and dimethyl carbonate in a volume ratio of 1:9) in which 1 M LiPF6 and 1.5 M lithium bis(fluorosulfonyl)imide were dissolved.

[0097] Example 5

[0098] A lithium secondary battery was manufactured in the same manner as in Example 1, except that a non-aqueous electrolyte solution was prepared by adding 2 g of vinylene carbonate (VC) and 1 g of propane sultone (PS) to 97 g of a non-aqueous organic solvent (a solvent mixture of ethylene carbonate and dimethyl carbonate in a volume ratio of 1:9) in which 2 M LiPF6 and 2 M lithium bis(fluorosulfonyl)imide were dissolved.

[0099] Comparative Example 1

[0100] A lithium secondary battery was manufactured in the same manner as in Example 1, except that a non-aqueous electrolyte solution was prepared by adding 2 g of vinylene carbonate (VC) and 1 g of propane sultone (PS) to 97 g of a non-aqueous organic solvent (a solvent mixture of ethylene carbonate and dimethyl carbonate in a volume ratio of 3:7) in which 0.5 M LiPF6 and 0.7 M lithium bis(fluorosulfonyl)imide were dissolved.

[0101] Comparative Example 2

[0102] A non-aqueous electrolyte solution was prepared by adding 2 g of vinylene carbonate (VC) and 1 g of propane sultone (PS) to 97 g of a non-aqueous organic solvent (a solvent mixture of ethylene carbonate and dimethyl carbonate in a volume ratio of 1:9) in which 3 M LiPF6 and 3 M lithium bis(fluorosulfonyl)imide were dissolved, but the prepared non-aqueous electrolyte was not suitable for batteries because the lithium salt was not completely dissolved.

[0103] Comparative Example 3

[0104] A lithium secondary battery was manufactured in the same manner as in Example 1, except that a non-aqueous electrolyte solution was prepared by adding 2 g of vinylene carbonate (VC) and 1 g of propane sultone (PS) to 97 g of a non-aqueous organic solvent (a solvent mixture of ethylene carbonate and dimethyl carbonate in a volume ratio of 1:9) in which 2M LiPF6 was dissolved.

[0105] Comparative Example 4

[0106] A lithium secondary battery was manufactured in the same manner as in Example 1, except that a non-aqueous electrolyte solution was prepared by adding 2 g of vinylene carbonate (VC) and 1 g of propane sultone (PS) to 97 g of a non-aqueous organic solvent (a solvent mixture of ethylene carbonate and dimethyl carbonate in a volume ratio of 1:9) in which 2 M lithium bis(fluorosulfonyl)imide was dissolved.

[0107] Comparative Example 5

[0108] A lithium secondary battery was manufactured in the same manner as in Example 1, except that LiNi 0.6 Co 0.2 Mn 0.2 O2(NCM622) as positive electrode active material instead of LiNi 0.8 Co 0.1 Mn 0.1 O2.

[0109] Comparative Example 6

[0110] A lithium secondary battery was manufactured in the same manner as in Comparative Example 1, except that LiNi 0.6 Co 0.2 Mn 0.2 O2 as positive electrode active material instead of LiNi 0.8 Co 0.1 Mn 0.1 O2.

[0111] Comparative Example 7

[0112] A lithium secondary battery was manufactured in the same manner as in Example 1, except that LiCoO2 (LCO) was used as the positive electrode active material instead of LiNi 0.8 Co 0.1 Mn 0.1 O2, and only graphite is used as the negative electrode active material instead of a mixture of graphite and SiO.

[0113] Comparative Example 8

[0114] A lithium secondary battery was manufactured in the same manner as in Comparative Example 1, except that LiCoO2 was used as the positive electrode active material instead of LiNi 0.8 Co 0.1 Mn 0.1 O2, and only graphite is used as the negative electrode active material instead of a mixture of graphite and SiO.

[0115] Comparative Example 9

[0116] A lithium secondary battery was manufactured in the same manner as in Example 1, except that only graphite was used as the negative electrode active material instead of the mixture of graphite and SiO.

[0117] [Table 1]

[0118]

[0119] Experimental Example 1: Evaluation of lifespan at room temperature

[0120] For the lithium secondary battery manufactured in the embodiment and the comparative example, the formation was performed with a current of 200 mA (0.1C rate), and then 100 cycles were performed with CC-CV charging at 4.2 V, 666 mA (0.33 C, 0.05 C cut-off) and CC discharge at 3 V, 666 mA (0.33 C). Then, when the discharge capacity in the first cycle was set to 100%, the ratio of the 100th discharge capacity was measured as the capacity retention rate, and the results are shown in Table 2 below.

[0121] [Table 2]

[0122] Capacity retention rate % Example 1 95 Example 2 94 Example 3 98 Example 4 94 Example 5 96 Comparative Example 1 90 Comparative Example 3 88 Comparative Example 4 92 Comparative Example 5 84 Comparative Example 6 85 Comparative Example 7 90 Comparative Example 8 90 Comparative Example 9 89

[0123] It can be confirmed from the above Table 2 that the secondary batteries manufactured according to Examples 1 and 5 of the present invention have excellent life characteristics compared with the secondary batteries manufactured according to Comparative Examples 1 to 9.

[0124] Experimental Example 2: Measurement of Initial DC Resistance

[0125] For each lithium secondary battery manufactured in Examples 1 to 5 and Comparative Examples 1, 3, 4 and 9, formation was performed with a current of 200 mA (0.1C rate), then CC-CV charging at 4.2 V, 666 mA (0.33 C, 0.05 C cut-off) and CC discharge at 3 V, 666 mA (0.33 C), repeated 3 cycles. Subsequently, the voltage drop was recorded, and the DC resistance value calculated using R = V / I (Ohm's law) is shown in Table 3 below.

[0126] [Table 3]

[0127] Initial resistance [Ohm] Example 1 0.038 Example 2 0.041 Example 3 0.035 Example 4 0.040 Example 5 0.043 Comparative Example 1 0.05 Comparative Example 3 0.062 Comparative Example 4 0.058 Comparative Example 9 0.05

[0128] As shown in [Table 3] above, the secondary batteries of Examples 1 to 5 exhibited low initial resistance compared to the secondary batteries of Comparative Examples 1, 3, 4, and 9. This result shows that the interface characteristics of the electrodes and the electrolyte of the secondary batteries of Examples 1 to 5 were stable and had excellent lithium ion mobility compared to the secondary batteries of Comparative Examples 1, 3, 4, and 9.

[0129] When the lithium concentration is low as in Comparative Example 1, it is difficult to form the SEI film and the lithium ion mobility is deteriorated, so the initial resistance increases.

[0130] When LiPF6 is applied alone as in Comparative Example 3, the lithium ion mobility is excellent, but it is difficult to form a stable SEI film on the surface of the negative electrode (especially the silicon active material), so the resistance increases, and when LiFSI is applied alone as in Comparative Example 4, the SEI film is stable, but as in Comparative Example 3, the lithium ion mobility is reduced, so the initial resistance of the battery increases.

[0131] Experimental Example 3: High Temperature Safety Evaluation

[0132] For each secondary battery manufactured in Examples 1 to 5, Comparative Examples 1 and 3, a HOT box test (an experiment in which a fully charged lithium secondary battery with SOC 100% is heated to 150°C at a heating rate of 5°C / min and left for 4 hours to check whether ignition occurs) is performed, which is an evaluation index for confirming high temperature durability. The measurement results are shown in Table 4 below.

[0133] In addition, the changes of voltage and temperature over time during the HOT box test of Example 1 and Comparative Example 3 are shown in Figure 1 and 2 middle. Figure 1 is a graph showing the HOT box test results of Example 1. Figure 2 is a graph showing the HOT cell test results of Comparative Example 3.

[0134] [Table 4]

[0135] Is it on fire? Fire start time (minutes) Example 1 X - Example 2 X - Example 3 X - Example 4 X - Example 5 X - Comparative Example 1 O 10 Comparative Example 3 X -

[0136] In Table 4, X represents the case where no ignition occurred during storage at 150° C., and O represents the case where ignition occurred during high-temperature storage.

[0137] Referring to Table 4, the lithium secondary batteries of Examples 1 to 5 did not catch fire at all when stored at high temperatures even when fully charged. This can be understood to mean that since the lithium secondary batteries of Examples 1 to 5 have excellent electrode interface stability, exothermic reactions are reduced and thermal runaway of the lithium secondary batteries is suppressed.

[0138] On the contrary, it can be observed that the lithium secondary battery of Comparative Example 1 catches fire during storage at 150°C. The positive electrode in the charged state is in a state of lithium ion deintercalation. Therefore, when the positive electrode is exposed to high temperature, the structure of the positive electrode collapses and oxygen free radicals are generated. The oxygen free radicals thus generated react exothermically with the electrolyte in the secondary battery, so that heat accumulates inside the battery, resulting in thermal contraction of the separator and internal short circuit of the secondary battery, and even accompanied by rapid thermal runaway, so the battery catches fire. Therefore, since the lithium secondary battery in which the interfacial adhesion between the electrode and the electrolyte of Comparative Example 1 is not improved has relatively weak high temperature stability, it can be observed that a fire occurs during storage at 150°C.

[0139] Meanwhile, in the case of Comparative Example 3, ignition did not occur. Figure 2 As shown in FIG. 1 , in the case of the lithium secondary battery of Comparative Example 3, a sharp voltage drop occurs at around 150° C. Figure 1 As shown, it can be observed that the voltage of the lithium secondary battery of Example 1 remained relatively constant during the HOT box test.

Claims

1. A lithium secondary battery, comprising: A positive electrode comprising a lithium nickel cobalt manganese-based positive electrode active material, wherein: Among all transition metals, the content of nickel is 80 mol% or more; A negative electrode comprising a silicon-based negative electrode active material and a carbon-based negative electrode active material with a weight ratio of 1:99 to 50:50; A separator; And A non-aqueous electrolyte solution, wherein the non-aqueous electrolyte solution comprises a non-aqueous organic solvent and a lithium salt, the concentration of the contained lithium salt is 1.8 M to 5 M, and the lithium salt comprises LiPF6 and lithium bis(fluorosulfonyl)imide.

2. The lithium secondary battery according to claim 1, in, the concentration of the lithium salt contained in the non-aqueous electrolyte solution is 2 M to 5 M.

3. The lithium secondary battery according to claim 1, in, the weight ratio of LiPF6 and lithium bis(fluorosulfonyl)imide contained is 1:9 to 5:

5.

4. The lithium secondary battery according to claim 1, in, the weight ratio of LiPF6 and lithium bis(fluorosulfonyl)imide contained is 1:4 to 1:1.

85.

5. The lithium secondary battery according to claim 1, in, the positive electrode active material is represented by the following Formula 1: [Formula 1] Li 1+x [Ni a Co b Mr c M d ]O2 wherein 0 ≤ x < 1, 0.8 ≤ a < 1, 0 < b < 0.2, 0 < c < 0.2, 0 ≤ d < 0.2, and M is at least one element selected from the group consisting of W, Cu, Fe, V, Cr, Ti, Zr, Zn, Al, Ta, Y, In, La, Sr, Ga, Sc, Gd, Sm, Ca, Ce, Nb, Mg, B, and Mo.

6. The lithium secondary battery according to claim 1, in, The silicon-based anode active material includes at least one selected from the group consisting of: metallic silicon (Si); silicon oxide SiO y , where 0 < y < 2; silicon carbide (SiC); and Si-Y alloy, where Y is an element selected from the group consisting of alkali metals, alkaline earth metals, group 13 elements, group 14 elements, transition metals, rare earth metals, and combinations thereof, and does not include Si.

7. The lithium secondary battery according to claim 1, in, the carbon-based negative electrode active material is selected from artificial graphite, natural graphite, graphitized carbon fiber, or amorphous carbon.

8. The lithium secondary battery according to claim 7, in, the weight ratio of the silicon-based negative electrode active material and the carbon-based negative electrode active material contained in the negative electrode is 5:95 to 30:

70.

9. The lithium secondary battery according to claim 1, in, the non-aqueous organic solvent includes at least one selected from the group consisting of cyclic carbonate solvents, linear carbonate solvents, ester solvents, and ether solvents.

10. The lithium secondary battery according to claim 9, in, the non-aqueous organic solvent contains 20% by volume or less of the cyclic carbonate solvents.